Pengembangan Pembelajaran Melalui Model Pembelajaran Kognitif - Yedia Syaranamual; Tanwey Gerson Ratumanan (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
In the dynamics of contemporary education, the development of critical, reflective, and constructive thinking has become an urgent need that must be addressed through appropriate instructional approaches. This study aims to examine how cognitive-based learning models can be implemented in developing contextual strategies that focus on nurturing students’ intellectual potential. This research employed a descriptive qualitative method through a literature review approach, systematically identifying and analyzing scholarly sources such as journals, books, and articles published between 2020 and 2025. The analysis reveals that cognitive learning models significantly impact students’ active engagement, the enhancement of higher-order thinking skills, and the formation of a sustainable knowledge structure. These strategies enable educators to design learning processes that are adaptive to students’ developmental stages and encourage meaningful learning through internal cognitive involvement